AN ANALYSIS ON STUDENTS’ DIFFICULTIES IN SPEAKING CLASS PRESENTATION - Muhammad Abdul Majid; Abdurrahim (Journal of Education, Teaching, and Learning, 2024)
This research focuses on the students’ speaking difficulties’ in public speaking (presentation) of eleventh grade students of SMK Taruna Bangsa Sakra Barat in school year 2019/2020 both linguistic and non linguistic problems. The purpose of this research is to find out the most dominant and least difficulties (problems) faced by the eleventh grade students in their public speaking (presentation). This research used descriptive method. There were 21 students to be participants in this study. The researcher used questionnaire as the tools of data collection. The finding showed that the most dominant problem faced by the students in doing the presentation is unfavorable environment (27.27%), and the least problem in doing the presentation is difficult in finding ideas (4.28%). The other problems are lack of small notes (20.45%), worried sentence not accordance with English structure (grammar) (10.71%), lack of vocabulary (9.35%), lack of confidence (8.31%), confuse caused by the differences of written and pronounce (7.14%), often lose ideas cause nervous (5.84%), Cannot transform the vocabularies into a sentences (5.71%), Unfamiliar with English (5.19%), and difficult in finding ideas (4.28%).